Edukasi Pentingnya Menjaga Kesehatan Mata Pada Siswa-Siswi SD Negeri Kompleks Sambung Jawa Kota Makassar - Salasa, Alfrida Monica (Jurusan Farmasi Politeknik Kesehatan Makassar, 2024)
Education On The Importance of Maintaining Eve Health in Students of State Primary School State Sambung Jaya Complex Makassar CityThe use of electronic devices, especially gadgets, too often and for long periods of time by children, especially those attending elementary school level, can have an impact on eye health. Education for elementary school students regarding eye health is one way to provide knowledge to elementary school students regarding this matter. This education is a form of community service activity. The aim of this activity is to increase the knowledge of students at the Sambung Jawa Complex Public Elementary School regarding eye health and increase children's awareness of maintaining eye health. The target of this activity is students at the Sambung Jawa Complex Public Elementary School, Makassar City. Activity Method: This activity is in the form of education carried out using the lecture method by presenting interesting material, showing videos and games related to eye health. The output of this activity is in the form of scientific articles published on devotional media and videos of activities uploaded on the youtube media platform which can be accessed at the following link: https://youtube.com/shorts/KTvdrnS8bE8 . The conclusion obtained by this activity went well and smoothly and there was an increase in the knowledge of the target audience by 91,67%.Penggunaan perangkat elektronik khususnya gadget yang terlalu sering dan dalam jangka waktu yang lama oleh anak-anak khususnya yang bersekolah pada tingkat Sekolah dasar dapat berdampak pada gangguan pada kesehatan mata. Edukasi terhadap siswa-siswi SD mengenai kesehatan mata merupakan salah satu cara untuk memberikan pengetahuan dan pemahaman kepada siswa-siswi SD mengenai hal tersebut. Tujuan kegiatan ini adalah untuk meningkatkan pengetahuan siswa-siswi SD Negeri Kompleks Sambung Jawa mengenai kesehatan mata serta meningkatkan kesadaran anak-anak dalam menjaga kesehatan mata. Khalayak sasaran dari kegiatan ini adalah Siswa-siswi SD Negeri Kompleks Sambung Jawa Kota Makassar. Metode Kegiatan: Kegiatan ini berupa sosialisasi dan edukasi yang dilakukan dengan metode ceramah dengan menampilkan materi yang menarik, penayangan video dan permainan interaktif yang berkaitan dengan kesehatan mata. Capaian luaran dari kegiatan pengabdian ini berupa artikel ilmiah yang dipublikasi pada media pengabdian dan video kegiatan yang diuplod pada pada platform media youtube yang dapat diakses pada link berikut : https://youtube.com/shorts/KTvdrnS8bE8. Kesimpulan yang diperoleh kegiatan ini berlangsung dengan baik dan lancar serta terdapatnya peningkatan pengetahuan khalayak sasaran sebesar 91,67%